The Rasch-rating scale model to identify learning difficulties of physics students based on self-regulation skills - Habibi Habibi; Jumadi Jumadi; Mundilarto Mundilarto (Institute of Advanced Engineering and Science, 2019)
This study applies the unidimensional Rasch Model assumptions in identifying physics learning difficulties based on students' self-regulation abilities. A total of 126 physics teacher candidates have been observed for one semester. Self-project as a learning strategy has been used. Data were collected using 20 items in rating scales and then analyzed quantitatively to get feasibility in measuring self-regulation skills. The results have shown that the profile items analyzed by the Rasch Model are feasible to measure self-regulation skills through a self-sustaining project strategy. Most physics teacher candidates have a medium ability of 51% in the process of self-regulation, high = 33%, and low = 16%. The implications of applying self-projects to the processes of self-regulation are discussed in this article.